Learning organizations and knowledge management: Which one enhances another one more? - Hossein Vazifeh Dust; Mahdiyeh Kalantari Dehaghi; Raheim Sadeghi Demneh (Management Science Letters)
This paper presents an empirical investigation to detect whether knowledge management (KM) promotes learning organization (LO) or vice versa. The proposed study tries to find out the positive influences of KM components including knowledge acquisition, sharing, and utilization with different LOs dimensions. The study was performed among managers and members of societies of software and computer engineering field in city of Tehran, Iran. One time knowledge management processes were seen as independent variable and another time considered as dependent variables. Pearson correlation and regression analysis were used to test the hypothesis. The results show that KM promotes OLs more than OLs promotes KM.